Comics in Translation - F. Zanettin; Zanettin, Federico (St Jerome, 2008)
Comics are a pervasive art form and an intrinsic part of the cultural fabric of most countries. And yet, relatively little has been written on the translation of comics. Comics in Translation attempts to address this gap in the literature and to offer the first and most comprehensive account of various aspects of a diverse range of social practices subsumed under the label 'comics'. Focusing on the role played by translation in shaping graphic narratives that appear in various formats, different contributors examine various aspects of this popular phenomenon. Topics covered include the impact of globalization and localization processes on the ways in which translated comics are embedded in cultures; the import of editorial and publishing practices; textual strategies adopted in translating comics, including the translation of culture- and language-specific features; and the interplay between visual and verbal messages. Comics in translation examines comics that originate in different cultures, belong to quite different genres, and are aimed at readers of different age groups and cultural backgrounds, from Disney comics to Art Spiegelman's Maus, from Katsuhiro Ōtomo's Akira to Goscinny and Uderzo's Astérix. The contributions are based on first-hand research and exemplify a wide range of approaches. Languages covered include English, Italian, Spanish, Arabic, French, German, Japanese and Inuit. The volume features illustrations from the works discussed and an extensive annotated bibliography. Contributors include: Raffaella Baccolini, Nadine Celotti, Adele D'Arcangelo, Catherine Delesse, Elena Di Giovanni, Heike Elisabeth Jüngst, Valerio Rota, Carmen Valero-Garcés, Federico Zanettin and Jehan Zitawi.